Orthodontic treatment of malocclusion cases with teeth after root canal treatment: Case report - Habar, Eddy H. (Hasanuddin University, 2024)
Objective: This case report discusses orthodontic treatment of malocclusion cases with teeth after root canal treatment.Method: A 24 year old woman came to the clinic with the main complaint of crowded teeth. Intra-oral examination revealed tooth rotation, palatoversion and edge to edge bite. Radiographic examination revealed teeth that had been treated with root canal treatment. Diagnosis is dental class I malocclusion.Result: Crowded teeth, rotation of teeth, palatoversion of teeth and edge to edge bite have been corrected. Interdigitation of the maxillary and mandibular teeth has been achieved.Conclusion: In this case the tooth after root canal treatment can be adjusted orthodontically